Characterization of Impulse Oscillometric Measures of Respiratory Small Airway Function in Children - Avila, Nancy (2019)
Abstract. Children suffering from asthma are often undiagnosed or misdiagnosed as their symptoms are similar to other respiratory conditions. Spirometry, the "golden" pulmonary function test used for asthma di- agnosis, is often unsuitable for young children since it requires them to perform extreme inhalation and exha- lation maneuvers. Impulse Oscillometry (IOS) is an effortless, child-friendly, sensitive, and reliable testing technique that could be used in the effective diagno- sis of asthma. However, the IOS requires a deep un- derstanding of the mechanical and/or equivalent elec- trical circuit models of the human respiratory system, which hinders its broad acceptance and utility in clin- ics. This paper presents a data characterization study based on the statistical assessment of the IOS param- eters. The main focus is to investigate four differ- ent manifestations of pulmonary conditions in chil- dren due to peripheral obstruction: Asthma (A), Small Airway Impairment (SAI), Possible Small Airway Im- pairment (PSAI), and Normal (N). The objective of this investigation is to pave the way for the feature se- lection stage of our future computer-aided classifica- tion work to distinguish between lung dysfunction and healthy lung function in children by identifying those IOS parameters that are most sensitive to discriminate between the different respiratory conditions mentioned above. Our ultimate goal is to facilitate the interpreta- tion of the impulse oscillometric test results and pro- vide clinicians with a reliable and proven method for accurate classification of children’s lung function for an early asthma detection, diagnosis, and control.